2011
DOI: 10.1371/journal.pone.0028695
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Wolbachia Infections in Natural Populations of Aphids: Is the Hidden Diversity Fully Unraveled?

Abstract: Aphids are a serious threat to agriculture, despite being a rather small group of insects. The about 4,000 species worldwide engage in highly interesting and complex relationships with their microbial fauna. One of the key symbionts in arthropods is Wolbachia, an α-Proteobacterium implicated in many important biological processes and believed to be a potential tool for biological control. Aphids were thought not to harbour Wolbachia; however, current data suggest that its presence in aphids has been missed, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
180
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(200 citation statements)
references
References 99 publications
(111 reference statements)
5
180
1
6
Order By: Relevance
“…Wolbachia strains are represented with the name of their host species. The scale value of 0.02 is marked with a red line, because the value was considered a threshold to establish new supergroups for Wolbachia (Augustinos et al., 2011). Sequence pairs concerning about w M yos infecting Mes.…”
Section: Resultsmentioning
confidence: 99%
“…Wolbachia strains are represented with the name of their host species. The scale value of 0.02 is marked with a red line, because the value was considered a threshold to establish new supergroups for Wolbachia (Augustinos et al., 2011). Sequence pairs concerning about w M yos infecting Mes.…”
Section: Resultsmentioning
confidence: 99%
“…It should be stressed that an earlier molecular analyses did not detect Wolbachia in aphids (Tsuchida et al, 2002). However, recent extensive studies have indicated that this bacterium occurs sporadically in some populations of representatives of several aphid families (Wang et al, 2009;Augustinos et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…The clade containing Wolbachia pipientis is divided into 11 to 13 supergroups, depending on the study (1,3,18). Wolbachia bacteria are maternally transmitted reproductive parasites (19,27).…”
mentioning
confidence: 99%